(untitled) (Research, Society and Development, 2021)
Comprehensive health care has been a challenge in the Brazilian context. In the pediatric scenario, there are important advances in health actions, but in practice there are still weaknesses that prevent them from actually materializing. In this context, the Urgency and Emergency Network is responsible for articulating health equipment, expanding and qualifying users’ access to different points or health services. Objective: to identify in the literature what are the reasons for seeking care in the emergency room. Method: This is a narrative review in the Virtual Health Library and SCOPUS, of the evidence published about the reasons for seeking care in the Emergency Room, from 2010 to 2020. Results: Predominance of studies that addressed the issues of care for urgency, its interfaces with the lack of protagonism in Primary Health Care, little emphasis on the pediatric population. Conclusion: The development of assistance in a network has been adopted, however in child care with an emphasis on the Urgency and Emergency Network, it has shown weaknesses in the articulation and communication in the network. The hospital has been seen as a place where all health problems are resolved.